Physically Interactive Story Environments - Wilson, Andy; Pinhanez, C. S.; Davis, J. W.; Intille, S.; Johnson, M. P.; Bobick, A. F.; Blumberg, B. (IBM Systems Journal, 2000)
Most interactive stories, such as hypertext narratives and interactive movies achieve an interactive “feel” by allowing the user to choose among multiple story paths. In this paper we discuss physically interactive environments with narrative structure in which the ability to choose among multiple story lines is replaced with having users, first, interact with the story characters in small, local “windows” of the narrative and, second, actively engage their bodies in movement. In particular, we found that compelling interactive narrative story systems can be perceived as highly responsive, engaging, and interactive even when the overall story has a single-path structure, in what we call a “lesschoice, more-responsiveness” approach to the design of story-based interactive environments. We have also observed that unencumbering, rich sensor technology can facilitate user immersion in the experience as the story progresses—users can act as they typically would without worrying about manipulating a computer interface. To support these arguments, the paper describes the physical setup, the interactive story, the technology, and the user experience of four projects developed at the MIT Media Laboratory: KidsRoom, It/I, Personal Aerobics Trainer, and Swamped!